PENDEKATAN KONSELING BEHAVIORAL TERHADAP PERKEMBANGAN MORAL SISWA - Laia, Bestari; Sarumaha, Murnihati; Zalukhu, Merri Christina; Ndruru, Mastawati; Telaumbanua, Tatema; Ndraha, Lies Dian Marsa; Harefa, Darmawan (Unversitas Katolik Santo Thomas, 2021)
The purpose of this study was to describe the level moral development of students before and after being treated, as well as to examine the behavioral counseling approach Â the moral development of students of SMP Negeri 1 Aramo. This research uses quantitative research with experimental research methods. The population in this study were all students of SMP Negeri 1 Aramo, totaling 200 students, and a sample of 25 students using purposive sampling technique. The data analysis technique in this study used simple linear regression analysis. Based on the results of the study, it was found that the level of moral development was in the high category with a percentage of 75.20% and an average score of students 88.94, 3) the coefficient of determination with value. Regression model which means rejected and accepted. It can be concluded there is a behavioral counseling approach to students' moral development